(untitled) (Journal of the College of Basic Education, 2023)
The Islamic Revolution in Iran is considered one of the most prominent political events in the Middle East. As it brought down the Pahlavi regime, which had ruled Iran for nearly half a century and was loyal to the West, especially the United States of America. That system (the Pahlavi regime) followed several modernizations within society, taking Western culture as its basis, and neglecting the conservative Islamic culture that exists in Iran in a very large way. The issue of women was one of the aspects of conflicts between the regime and the religious institution, until the men of religious institution were able to overthrow the Pahlavi rule represented by Shah Muhammad Reza in 1979. After the victory of the revolution, it is naturally that there are several political developments that Iranian women must take a stand on, and there are also some decisions taken by Mr. Khomeini towards women.